Comparative evaluation of antihypertensive drugs in the management of pregnancy-induced hypertension - Patel, Nita K.; Gadhavi, Mansi; Gorasia, Dhaval; Pandya, Manish R. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Pregnancy-induced hypertension is associated with various adverse fetal and maternal outcomes. The use of anti-hypertensive drugs in pregnancy is controversial. We conducted a prospective study to evaluate the comparative effectiveness and safety of nifedipine, methyldopa and labetalol monotherapy in patients with pregnancy-induced hypertension. Methods: A total of 60 pregnant women with blood pressure of 140/90 mm Hg or more with ≥1+ proteinuria between 20 and 38 weeks of gestation were randomly allocated to receive nifedipine (n=20), methyldopa (n=20) or labetalol (n=20). Blood pressure was measured at 0, 6, 24, 48 and 72 h of initiation of antihypertensive drugs. Patients were also followed up for development of adverse drug effects during this period. Results: Antihypertensive treatment with methyldopa was associated with reduction in systolic blood pressure (SBP) by 50 mmHg and diastolic blood pressure (DBP) by 30 mmHg at 72 h. For the same period treatment with nifedipine was associated with reduction in SBP by 54 mmHg and DBP by 30 mmHg. Treatment with labetalol was associated with reduction in SBP by 70 mmHg and DBP by 36 mmHg at 72 h. Conclusions: Labetalol was more effective than methyldopa and nifedipine in controlling blood pressure in patients with pregnancy-induced hypertension while methyldopa and nifedipine are equally effective in controlling blood pressure.